Administrasi Sekolah: Tinjauan Administrasi Keuangan, Perlengkapan, Hubungan Sekolah dengan Masyarakat - Parida Parida; Lias Hasibuan; Kasful Anwar; Ahmad Fadhil Rizki (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Financial administration, equipment, school relations with the community are carried out in an effort to improve the quality of education in schools. The method used in writing this paper is qualitative by using a literature study, namely by finding and analyzing journals or reading sources related to the papers discussed. In implementing educational supervision, financial administration, completeness and relations between schools and the community must be considered. In addition, improving the relationship between the scope of the school and the relationship between the community also needs to be improved in order to form supervision in the world of education based on improving the quality of education in schools. In the supervision of education, it is necessary to have a model or strategy that is useful to increase the scope of the study. In this case, financial administration, equipment, school relations with the community are carried out in an effort to improve the quality of education in schools.